Nanoscale coordination polymer Fe-DMY downregulating Poldip2-Nox4-H2O2 pathway and alleviating diabetic retinopathy - Si-Yu Gui; Xin-Chen Wang; Zhi-Hao Huang; Mei-Mei Li; Jia-Hao Wang; Si-Yin Gui; Gan-Hua Zhang; Yao Lu; Li-Ming Tao; Hai-Sheng Qian; Zheng-Xuan Jiang (Elsevier, 2023)
Diabetic retinopathy (DR) is a prevalent microvascular complication of diabetes and the leading cause of blindness and severe visual impairment in adults. The high levels of glucose trigger multiple intracellular oxidative stress pathways, such as POLDIP2, resulting in excessive reactive oxygen species (ROS) production and increased expression of vascular cell adhesion molecule-1 (VCAM-1), hypoxia-inducible factor 1α (HIF-1α), and vascular endothelial growth factor (VEGF), causing microvascular dysfunction. Dihydromyricetin (DMY) is a natural flavonoid small molecule antioxidant. However, it exhibits poor solubility in physiological environments, has a short half-life in vivo, and has low oral bioavailability. In this study, we present, for the first time, the synthesis of ultra-small Fe-DMY nano-coordinated polymer particles (Fe-DMY NCPs), formed by combining DMY with low-toxicity iron ions. In vitro and in vivo experiments confirm that Fe-DMY NCPs alleviate oxidative stress-induced damage to vascular endothelial cells by high glucose, scavenge excess ROS, and improve pathological features of DR, such as retinal vascular leakage and neovascularization. Mechanistic validation indicates that Fe-DMY NCPs can inhibit the activation of the Poldip2-Nox4-H2O2 signaling pathway and downregulate vital vascular function indicators such as VCAM-1, HIF-1α, and VEGF. These findings suggest that Fe-DMY NCPs could serve as a safe and effective antioxidant and microangio-protective agent, with the potential as a novel multimeric drug for DR therapy.